2016
DOI: 10.1016/j.ejso.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The interval between primary melanoma excision and sentinel node biopsy is not associated with survival in sentinel node positive patients – An EORTC Melanoma Group study

Abstract: SynopsisThis study examines >1000 sentinel node (SN) positive melanoma patients. Time interval between primary excision and SN biopsy (SNB) is no prognostic factor for disease free and melanoma specific survival. Guidelines advocating SNB <6 weeks should be reconsidered. M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 AbstractBackground: Worldwide, sentinel node biopsy (SNB) is the recommended staging procedure for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…These results are in keeping with those of Parrett and colleagues 7 and Oude Ophuis and colleagues. 10 Our findings are validated using data from the multinational, prospective MSLT-1 dataset, where delays of less than 30 vs 30 or more days between time of initial diagnosis and definitive surgery had no impact on DFS or MSS in all patients, with and without positive sentinel nodes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These results are in keeping with those of Parrett and colleagues 7 and Oude Ophuis and colleagues. 10 Our findings are validated using data from the multinational, prospective MSLT-1 dataset, where delays of less than 30 vs 30 or more days between time of initial diagnosis and definitive surgery had no impact on DFS or MSS in all patients, with and without positive sentinel nodes.…”
Section: Discussionsupporting
confidence: 56%
“…7 Similarly, a series reported by the European Organization for Research and Treatment of Cancer Melanoma Group, which included 1,015 sentinel lymph node-positive patients with a median time of 47 days from diagnosis to definitive surgery, and demonstrated that “delay” time had no impact on 5-year MSS (p = 0.72) and was not an independent prognostic factor for MSS (p = .57). 10 …”
Section: Discussionmentioning
confidence: 99%
“…An update to 2016 was performed in order to include long‐term follow‐up data. Date of diagnosis and date of SNB had been collected previously.…”
Section: Methodsmentioning
confidence: 99%
“…stated that early SNB had a positive effect on the survival of SN‐positive patients. Oude Ophuis and colleagues also investigated this topic, and found no difference in survival in a larger series of 1015 SN‐positive patients; nor did the timing of SNB influence SN positivity in a group of 3546 SN‐positive and ‐negative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with suspected melanoma must have a diagnostic excision within 1 week and be referred to be staged within 3 weeks. However, for early stage patients who have had a radical diagnostic excision, the time taken for a sentinel node procedure is not relevant to prognosis (Nelson et al, 2017;Oude Ophuis et al, 2016). …”
Section: Care Pathways and Timelinesmentioning
confidence: 99%